Students' Attitudes towards Using Microsoft Teams Platform in English Language Instruction - Danijela M. Prošić-Santovac; Vesna V. Bulatović; Tanja P. Kaurin (University of Belgrade, Teacher Education Faculty, 2021)
Information technology (IT) can greatly contribute to the efficiency of the educational process by providing teachers with a variety of educational activities. However, apart from obvious advantages in terms of new organizational forms of teaching, there are also potential challenges. Organizing foreign language classes, and in this paper we focus on English language classes, only in online format is a specific challenge. Microsoft Teams platform, supported with selected applications and functions provided by the platform, was used for English classes. These applications and functions were used for improving students' language skills: 1) OneNote Notebook and Chat for developing writing skills, 2) News for developing reading skills, 3) Microsoft Stream and Speech Recognition for developing speaking skills, and 4) Sharing the Screen for developing listening skills. The participants in the research were students of the upper-intermediate level English course who attended the entire course online and they were surveyed with the aim of collecting information about their attitudes towards the platform, applications, and functions. Based on their responses to open-ended and close-ended questions, it may also be concluded that for the majority the experience with attending the online English course is positive. The research results indicate that the potential of using the Microsoft Teams platform in teaching English language is considerable and that the platform, apart from its simple and functional interface, provides an opportunity for improving language skills in an innovative, interactive, and stimulating environment.